2022
DOI: 10.1037/apl0000920
|View full text |Cite
|
Sign up to set email alerts
|

Multiple jobholding motivations and experiences: A typology and latent profile analysis.

Abstract: Researchers have traditionally suggested that multiple jobholders (MJHers; individuals who work more than one job) are economically deprived and piece together employment to make ends meet. More recently, scholars have demonstrated that MJHers are also motivated for nonpecuniary benefits. In the current research, we employ a mixed-methods, three-study research design on 1,487 MJHers to develop a comprehensive typology of multiple jobholding (MJH) motivations, advance our understanding of how MJH motivations co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 133 publications
1
26
0
1
Order By: Relevance
“…We again found that total income and general side-hustle autonomy did not moderate the relationships in our model. Given that financial need and personal interest in the work represent key motives for side-hustles (Ashford et al, 2018;Ravenelle, 2019), we tested the moderating effects of these two motives using the respective six-item and four-item measures from Campion and Csillag (2022). Neither motive moderated the various stages of our model.…”
Section: Study 2: Supplemental Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…We again found that total income and general side-hustle autonomy did not moderate the relationships in our model. Given that financial need and personal interest in the work represent key motives for side-hustles (Ashford et al, 2018;Ravenelle, 2019), we tested the moderating effects of these two motives using the respective six-item and four-item measures from Campion and Csillag (2022). Neither motive moderated the various stages of our model.…”
Section: Study 2: Supplemental Analysesmentioning
confidence: 99%
“…4–5) argued that a person’s reaction is a “direct function of the unique instrumental value which the [threatened] behavior has for the satisfaction of needs.” Employees have an innate need to decide when, where, and how to work (Cable & Edwards, 2004; Deci & Ryan, 2000; Hackman & Oldham, 1976; Schwartz, 1992). Indeed, many employees adopt side-hustles precisely because they fulfill this need (Campion & Csillag, 2022).…”
Section: Theory Developmentmentioning
confidence: 99%
“…To advance our understanding of how employee withdrawal states are different across two countries, we use this person-centered approach. Previous studies on multiple job holding motivations and vocational research have similarly adopted person-centered approach and brought new insights into their literature (e.g., Campion & Csillag, 2022; Spurk et al, 2020). Thus, we followed best practices as described in previous research (e.g., Nylund et al, 2007; Spurk et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…For example, some organizations may hire just about any applicant who meets basic qualifications (e.g., at least 18 years of age, acceptable driving record, clean drug test). Another issue is how organizations perceive applicants for traditional jobs who also hold a gig job (i.e., multiple jobholders, E. D. Campion & Csillag, 2022). Gig workers are more likely to be racial minorities (particularly Hispanic and Black individuals), as well as from lower income levels (Pew Research Center, 2021).…”
Section: Selection For Gig and Telework Workmentioning
confidence: 99%